Clinical Expertise Is Core to an Evidence-Based Approach to Auditory Processing Disorder: A Reply to Neijenhuis et al. 2019 - Iliadou, Vasiliki; Kiese-Himmel, Christiane; Bamiou, Doris-Eva; Grech, Helen; Ptok, Martin; Chermak, Gail D.; Thai-Van, Hung; Stokkereit Mattsson, Tone; Musiek, Frank E. (Frontiers in Neurology, 2019)
The opinion article “An Evidence-based Perspective on Misconceptions Regarding Pediatric Auditory Processing Disorder” by Neijenhuis, Campbell, Cromb et al. (1) presents a distorted view of the evi-dence-based approach used in medicine. The authors focus on the amorphous non-diagnostic entity ‘listening difficulties’ not auditory processing disorder (APD) and create confusion that could jeop-ardize clinical services to individuals with APD. In our perspective article, we rebut Neijenhuis et al 2019, and more importantly, we present a rationale for  evidence-based practice founded on the prem-ise that research on APD is only clinically applicable when conducted on clinical populations diag-nosed with APD.